2019
DOI: 10.21307/pm-2019.58.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota In Chronic Kidney Disease

Abstract: In health, the relationship between gut microflora and the host is of a mutualistic kind. Microbiota offers many benefits to the host, including harvesting energy, regulating host immunity, and the synthesis of vitamins. Alteration in gut microflora can lead to homeostasis disruption and development of various diseases. Dysbiosis is commonly observed in chronic kidney disease (CKD). Nutrient processing by gut microbiota results in the production of some uremic toxins, and these accumulate in CKD causing delete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Authors reported ( 77 ) decrease in the anaerobic microflora in patients with CKD, while an increase of the aerobic microflora background ( 78 ) is observed with a predominance of Enterobacteriaceae ( 79 ). As previously discussed gut microbiota in healthy recipients possess three main enterotypes ( 80 ): Bacteroides, Prevotella , or Ruminococcus .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Authors reported ( 77 ) decrease in the anaerobic microflora in patients with CKD, while an increase of the aerobic microflora background ( 78 ) is observed with a predominance of Enterobacteriaceae ( 79 ). As previously discussed gut microbiota in healthy recipients possess three main enterotypes ( 80 ): Bacteroides, Prevotella , or Ruminococcus .…”
Section: Introductionmentioning
confidence: 99%
“…As previously discussed gut microbiota in healthy recipients possess three main enterotypes ( 80 ): Bacteroides, Prevotella , or Ruminococcus . As previously stated, the gut microbiota in patients with CKD is shifted, characterized by low numbers of Lactobacillaceae and Prevotellaceae families and higher Enterobacteria and Enterococci ( 79 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations